Test-retest reliability of a visual-cognitive technology (BlazePod™) to measure response time - de-Oliveira, L. A.; Matos, M. V.; Fernandes, I. G. S.; Nascimento, D. A.; da Silva-Grigoletto, M. E. (Journal of Sports Science & Medicine, 2021)
A new technology (BlazePod™) that measures response time (RT) is currently on the market and has been used by strength and conditioning professionals. Nevertheless, to trust in the measurement, before the use of a new device to measure any outcome in the research or clinical setting, a reliability analysis of its measurement must be established (Koo and Li, 2016). Hence, we assessed the test-retest reliability (repeatability) of the BlazePod™ (Play Coyotta Ltd., Aviv, Israel) technology during a pre-defined activity to provide information about the level of agreement and the magnitude of errors incurred when using the technology. This information can assist practitioners and researchers in the use of BlazePod™ technology.